The Level Of Narcissistic Tendencies Of Junior High School Students In Superior Classes - Islammika, Intan; Sano, Afrizal (Consilium, 2023)
This type of research is descriptive with a research subject of 96 students. The sampling technique used was purposive sampling. The data collection instrument was a questionnaire on the level of students' narcissistic tendencies using a Likert scale. The results of this study revealed that: (1) The level of narcissistic tendencies of superior class students as a whole belongs to the High category, (2) The level of narcissistic tendencies of superior class students in the authory aspect is included in the medium category, (3) The level of narcissistic tendencies of superior class students in the aspect of self-sufficiency is included in the medium category, (4) The level of narcissistic tendencies of superior class students in the aspect of superiority is included in the high category, (5) The level of narcissistic tendencies of superior class students in the aspect of exhibitionism is included in the high category, (6) The level of narcissistic tendencies of superior class students on the aspect of exploitativeness included in the high category, (7) The level of narcissistic tendencies of superior class students in the vanity aspect is included in the high category, (8) The level of narcissistic tendencies of superior class students in the entitlement aspect is included in the high category.Based on the findings of this study, it is expected that counseling teachers or counselors can provide assistance in the form of Guidance and Counseling services.